The Influence of Health Consciousness, Social Media Marketing, and Electronic Word-of-Mouth (eWOM) on Purchase Intention through Attitude towards Stevia Natural Sweetener Products - Erika Shofia Faradysa; Andrian Haro; Meta Bara Berutu (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The increasing prevalence of metabolic diseases and the imbalance between sugar production and consumption in Indonesia have intensified interest in alternative sweeteners such as Stevia. This study aims to examine the effects of health consciousness, social media marketing, and electronic word-of-mouth (eWOM) on consumers’ purchase intention toward Stevia products, with attitude serving as a mediating variable. A quantitative survey was conducted among 250 urban consumers in Jakarta who were familiar with Stevia and actively used social media. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results indicate that health consciousness, social media marketing, and eWOM significantly influence consumer attitudes and purchase intention, both directly and indirectly. Attitude emerges as the strongest predictor of purchase intention and acts as a significant partial mediator in all examined relationships. The model demonstrates moderate explanatory and predictive power, confirming its robustness. These findings support the Theory of Planned Behavior within the functional food context and highlight that consumer purchase intention toward Stevia is primarily shaped through positive attitudinal formation rather than direct promotional exposure alone. The study implies that effective marketing strategies for alternative sweeteners should prioritize health-oriented education, credible social media engagement, and authentic peer communication to strengthen consumer attitudes, thereby supporting public health objectives and national food security.